At the margins of globalization : indigenous peoples and international economic law - Puig, Sergio (Cambridge : Cambridge University Press, 2021)
Despite the tremendous progress in the development of scientific knowledge, the understanding of the causes of poverty and inequality, and the role of politics and governance in addressing modern challenges, issues such as social inclusion, poverty, marginalization and despair continue to be a reality across the world - and most often impact Indigenous Peoples. At the Margins of Globalization explores how Indigenous Peoples are affected by globalization, and the culture of individual choice without responsibility that it promotes, while addressing what can be done about it. Though international trade and investment agreements are unlikely to go away, the inclusion of Indigenous rights provisions has made a positive difference. This book explains how these provisions operate and how to build from their limited success.
Title from publisher's bibliographic system (viewed on 27 Apr 2021).
Keywords: Indigenous peoples -- Economic conditions; Globalization -- Economic aspects